Apuntes sobre los orígenes del nacionalismo territorial argentino - Carlos Escudé (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2008)
– One important cultural factor that has contributed to inhibiting regional cooperation and integration in Latin America lies in the intense territorial nationalism prevailing in some of its Spanish-speaking countries. This frequently understated phenomenon is an outgrowth of the territorial disputes inherited from Colonial times, and of the indoctrination of public opinion through the educational system and the mass media. Indeed, nearly all of the Spanish-speaking countries of South America harbor myths of territorial losses. If the territories allegedly lost were added together, the resulting sum would be far greater than the actual land mass of South America. The Argentine case is particularly significant because of the Falkland/Malvinas War of 1982. Additionally, unlike its neighbors, a myth of national superiority, manifest destiny included, can also be identified in the Argentine curriculum of past decades, which helps to understand why it is the only South American state that took the matter as far as waging war against the second most powerful member of NATO, for the sake of atempting the recovery of a territory lost in 1833. The present article is part of a research program, undertaken by the author, that seeks to understand the cultural factors that not only made such a war popular, but also culminated in the inclusion of a clause, in the 1994 Constitution of Argentina, whereby it is the obligation of Argentine governments to strive for the recovery of the Falkland/Malvinas Islands. More broadly stated, this paper and the other products of this research program strive to contribute to the undertanding of the specific mechanisms through which culture sometimes conditions and limits socio-economic development, through its impact upon foreign policy. Paper # 310 of the CEMA series, 'Cultura política, política exterior y caducidad del modelo del Estado como actor racional: el caso argentino', corresponds to a different stage of the same research program.
Keywords: 330